Automating measurement process to improve quality management for piping fabrication. (August 2015) - Safa, Mahdi; Shahi, Arash; Nahangi, Mohammad; Haas, Carl; Noori, Hamid
Abstract: Addressing deficiencies and defects that occur during construction projects, particularly in piping fabrication, is costly and time consuming. The current quality management process associated with piping fabrication has a number of limitations, resulting primarily from human error and lack of consistency. This research therefore introduces an automated process for construction quality management that employs automated technologies for detecting defects, to contribute to the existing body of knowledge. The system relies on piping construction data collected with the use of photogrammetry and laser scanning, which are then used as a means of comparing the work actually performed to that designed. The developed three-station quality management model has the potential to decrease the overall cost of a project by reducing the fabrication rework required as well as by avoiding costly and time-consuming site assembly realignments, which are often caused by defects in the fabrication and delivery processes.